Mechanical Behavior of Concrete Reinforced with Natural Palm and Mango Fibers - Flores Nicolás, Alejandro; Flores Nicolás, Mario; Menchaca Campos, Elsa Carmina; Uruchurtu Chavarín, Jorge (Directorate for Research and Community Services, Institut Teknologi Bandung, 2025)
The search for new natural materials as reinforcement in concrete has increased as an economic and ecological alternative. The purpose of this work is to study the behavior of natural mango (mangifera indica) and palm fibers without treatment, incorporated into concrete to improve its mechanical properties. The physical properties of the coarse (gravel) and fine (sand) aggregates were analyzed, as well as the physical and mechanical characteristics of the fibers used in this research. Concrete mixtures were prepared incorporating 0.2% and 0.4% fiber content with respect to the weight of fine aggregate and a fiber length of 10 and 30 mm respectively. The experimental results showed that all the fibers used in different concentrations decreased the workability and air content of the concrete paste, consequently, the porosity had a downward trend. Short mango fibers at 0.4% concentration and palm fiber at 0.2% increase the compressive strength by 12% compared to the control sample.